RISE - Readiness for Investment in Sustainable Energy : A Tool for Policy Makers - World Bank Group (Washington, DC, 2014)
Readiness for Investment in Sustainable Energy (RISE) is a suite of indicators that assesses the legal and regulatory environment for investment in sustainable energy. It establishes a framework for better depicting the national enabling environment to attract investment into sustainable energy. In this way, RISE supports the achievement of the objectives of the Sustainable Energy for All initiative (SE4ALL): ensure universal access to modern energy services, double the share of renewable energy in the global energy mix, and double the rate of improvement in energy efficiency by 2030. Reaching the SE4ALL goals will require an almost tripling of historical annual investment flows in these areas to about $1 trillion, such that countries will need to embrace an enabling environment that attracts all forms of investment public and private. This report presents the methodology and results of a pilot phase of RISE involving 17 developed and developing countries, as well as an in-depth case study on Kenya. The pilot is supported by data collected between December 2013 and June 2014. The pilot countries, representing varying status in data availability and data quality are: Armenia, Chile, Denmark, Ethiopia, Honduras, India, Kenya, Liberia, Maldives, Mali, Mongolia, Nepal, the Solomon Islands, Tanzania, the United States, Vanuatu, and the Republic of Yemen. An in-depth exercise was carried out in Kenya to understand better progress in creating an enabling environment. This pilot report will be the starting point for launching the global rollout. It allows for a validation of the methodology, and for lessons learned from developing and implementing the suite of indicators across these countries. Most important, it will remain a baseline consultation document for the global rollout-expected in 2015 and to cover about 100 countries-helping refine the methodology and interpretation or results.